Optimization of Brain Function Learning (Neocortex) Through Neuroscience Based on Islamic Literature to Improve Behavior of Primary Students - Zulfitria Zulfitria; Zainal Arif; Tyasti Aryandini (STAI Hubbulwathan Duri, 2022)
Deep networks in human brain can develop representations that are a better match to recordings in the neocortex of humans as existing models in neuroscience. This suggests that deep learning captures something important about how our own brains works. Islamic education curriculum neuroscience such as Islamic manners lesson, apply learning methods for the development of intellect learners so in the formation of character can maximize the performance of sense and neuroscience of learning students are given the opportunity to actively construct knowledge through learning, thus neuroscience learning combined with a variety of disciplines so integrated into the mainstream of the formation of character especially character of polite and disciplined through Islamic literacy lesson. This research uses mixed methods these following approaches; Literature study and also Class Action Research in three cycles. The results of these research Educational Neuroscience as one of the fields of study of neuroscience specializes in its studies in the field of education from a neuroscience perspective.In learning Islamic fairy tale literacy which was carried out on 3rd grade students of SDIT Aulady, with three students as the object of this research, 3 models of Islamic fairy tale literacy learning were carried out.